Genetic interplay with soccer ball heading - Smith, D. H.; Stewart, W. (Nature Reviews Neurology, 2020)
Mortality from neurodegenerative disease is high among professional soccer players, potentially associated with repeated head impacts during routine gameplay. New data suggest that the apolipoprotein E e4 allele might exacerbate the effects of soccer ball heading on cognition. However, genotyping of athletes to determine their dementia risk remains a distant prospect.